2013
DOI: 10.7205/milmed-d-12-00490
|View full text |Cite
|
Sign up to set email alerts
|

Tourniquets and Occlusion: The Pressure of Design

Abstract: Limb circumference/tourniquet width occlusion pressure predictions are not good substitutes for measurements. The wider SWAT-T has lower occlusion and completion pressures than the CAT. Decreases in muscle tension lead to decreases in tourniquet pressure, especially with the nonelastic CAT, which can lead to occlusion loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 19 publications
0
19
0
7
Order By: Relevance
“…Застосовували смужку еластич-ного джгута "SWAT-T" (США) шириною 10 мм, що відповідає ширині джгута при накладанні на стегно дорослій людині. Такий джгут характери-зується мінімальним негативним впливом на під-леглі тканини за рахунок своєї ширини і тривалим у часі больовим порогом [10]. Джгут затягували відповідно до нанесеного на ньому індикатора ефективного тиску, який припиняє кровотік.…”
Section: експериментальні дослідженняunclassified
See 1 more Smart Citation
“…Застосовували смужку еластич-ного джгута "SWAT-T" (США) шириною 10 мм, що відповідає ширині джгута при накладанні на стегно дорослій людині. Такий джгут характери-зується мінімальним негативним впливом на під-леглі тканини за рахунок своєї ширини і тривалим у часі больовим порогом [10]. Джгут затягували відповідно до нанесеного на ньому індикатора ефективного тиску, який припиняє кровотік.…”
Section: експериментальні дослідженняunclassified
“…Да-датково здійснювали контроль якості накладання за допомогою реографічного методу. Характер-ною рисою джгута "SWAT-T" є ефективна зупин-ка артеріального кровотоку протягом усього тер-міну експерименту [10]. Тварин дослідних груп виводили з експерименту в умовах тіопентало-на-трієвого наркозу (60 мг·кг -1 ) методом тотального кровопускання із серця через 60 хв, 120 хв, 24 год, 7 і 14 діб після реперфузії.…”
Section: експериментальні дослідженняunclassified
“…Summary points that tourniquets need to stop arterial flow, 15 that tourniquets are most lifesaving applied before shock, 1,19 that effective wider tourniquets allow arterial occlusion at lower pressures, 13,14 that forearm and lower leg are acceptable tourniquet locations, 16,17 and that it is important to recheck tourniquets frequently to ensure that arterial occlusion pressures are maintained. 14 The tourniquets available for the attendees to handle were Combat Application Tourniquets (CAT, Composite Resources, Rock Hill, SC), Stretch Wrap And Tuck-Tourniquets (SWAT-T, TEMS Solutions, Abingdon, VA), Ratcheting Medical Tourniquets (RMT, m2 Inc., Winooski, VT), and a Mechanical Advantage Tourniquet (MAT, Pyng Medical Corp., Richmond, Canada). Attendees were allowed to apply any of the tourniquets to themselves, to other willing attendees, or to the presenters.…”
mentioning
confidence: 99%
“…The three important tourniquet concepts asked about were (1) the relationship between tourniquet width and pressure for arterial occlusion (an open-ended question regarding the understanding that wider tourniquets require less pressure for arterial occlusion 13,14 ), (2) the importance of achieving arterial occlusion (a multiple-choice question regarding the understanding that venous occlusion without arterial occlusion is harmful 15 ), and (3) appropriate extremity locations for tourniquets (on the most distal limb segment proximal to the injury 16,17 Va multiple-choice hand question and a multiple-choice foot question were asked to address this concept). Each of the concept questions, including the open-ended question, specifically had ''don't know'' as an available answer choice.…”
mentioning
confidence: 99%
“…The C-A-T has been shown to be superior to other tourniquets in controlling (minimizing) blood flow. 15,29 Savage et al 30 conducted a prospective controlled trial, comparing the efficacy and ease of applicability of 3 types of commercially available windlass tourniquets in 4 tactical situations on simulated patients. The overall finding of this study indicated that the C-A-T was applied the fastest in each scenario and was also significantly the most effective in occluding distal blood flow.…”
mentioning
confidence: 99%